Evidence for understanding the implications of improving the dietary quality of school lunches - Joyce, Jillian (Kansas State University, 2018)
The overall aim of this dissertation was to better understand the implications of improving the dietary quality (DQ) of school lunches. Chapter 2 includes a cross-sectional content analysis to determine whether there were significant differences in nutrient content and DQ between a best practice school lunch menu (BPM, with maximized DQ, created regardless of feasibility) and a typical school lunch menu (TM, with average DQ, from an actual school district). Results showed large significant differences in several important macro- and micro-nutrients and in DQ, favoring the BPM. These findings suggest the possibility for statistically and clinically significant variation in nutrient content and DQ of school lunches meeting National School Lunch Program (NSLP) nutrition standards. Building on that possibility for variation, and given schools report financial concerns as barriers to providing high DQ lunches, chapter 3 describes a cross-sectional content analysis to determine whether there were significant differences in nutrient content and DQ between middle school lunch menus from 85 Kansas school districts by socioeconomic status (SES) and rurality. The average DQ across all districts was 62.0±4.0 (Healthy Eating Index (HEI) score) out of 100, indicating a need for improvement. There were minimal differences in nutrient content and DQ by SES and rurality, suggesting efforts to improve DQ of Kansas school lunches should be applied equally across all SES and rurality categories. To determine best practices for improving DQ of school lunches, chapter 4 includes a critical review with the aim of developing school lunch best practices based on child DQ recommendations, and implementation techniques encouraging selection and consumption of healthier school lunches. Twenty-five articles were synthesized, creating a list of evidence-based school lunch best practices. Findings provide evidence that if implemented during menu and service planning, these best practices may help to improve school lunch DQ and increase selection and consumption of higher DQ lunches by schoolchildren. With best practices determined, chapter 5 describes a randomized crossover trial that included 36 elementary school-aged participants for the purpose of investigating the acceptability and feasibility of best practice school lunches (BPSL, implementing best practices, HEI score=90–95/100) as compared to typical school lunches (TSL, meeting baseline NSLP nutrition standards, HEI score=70–75/100). Results showed minimal differences in acceptability (taste, plate waste, and hunger) and feasibility (cost, equipment, and skill to prepare meals). However, preparation time requirements for BPSL were significantly longer than for TSL (~four-fold). When BPSL and TSL were offered concurrently, participants selected TSL significantly more frequently than BPSL (TSL=83.3%, BPSL=16.7%). These findings suggest that BPSL may be as acceptable and feasible as TSL, but when served concurrently, schoolchildren will likely choose the TSL. Collectively, results from this dissertation provide evidence that there is a need for improvement in the DQ of school lunches across the state of KS, which is likely to be feasible and acceptable, challenging previously reported barriers. This improvement may be accomplished by implementing best practices for higher DQ school lunches across rurality and SES categories. Collectively, these results could inform key stakeholders in policy- and decision-making.
Keywords: Child nutrition; School nutrition; Child; Adolescent; Nutrient contentDietary quality